Bioactive Seed Layer for Surface‐Confined Self‐Assembly of Peptides1. (14th July 2015) - Vigier‐Carrière, Cécile; Garnier, Tony; Wagner, Déborah; Lavalle, Philippe; Rabineau, Morgane; Hemmerlé, Joseph; Senger, Bernard; Schaaf, Pierre; Boulmedais, Fouzia; Jierry, Loïc
Abstract The design and control of molecular systems that self‐assemble spontaneously and exclusively at or near an interface represents a real scientific challenge. We present here a new concept, an active seed layer that allows to overcome this challenge. It is based on enzyme‐assisted self‐assembly. An enzyme, alkaline phosphatase, which transforms an original peptide, Fmoc‐FFY(PO42−), into an efficient gelation agent by dephosphorylation, is embedded in a polyelectrolyte multilayer and constitutes the "reaction motor". A seed layer composed of a polyelectrolyte covalently modified by anchoring hydrogelator peptides constitutes the top of the multilayer. This layer is the nucleation site for the Fmoc‐FFY peptide self‐assembly. When such a film is brought in contact with a Fmoc‐FFY(PO42−) solution, a nanofiber network starts to form almost instantaneously which extents up to several micrometers into the solution after several hours. We demonstrate that the active seed layer allows convenient control over the self‐assembly kinetics and the geometric features of the fiber network simply by changing its peptide density.